Optimal design of carbon and glass reinforced hybrid composite pipes under flexural loading - Dong, Chensong (2021)
This paper presents a study on the optimal design of carbon and glass reinforced hybrid composite pipes under flexural loading. The failure of composite pipes in three point bending was modelled numerically by Finite Element Analysis (FEA). Optimisation on hybrid composite pipes under flexural loading was conducted using non-dominated sorting GA-II (NSGA-II) with minimum cost and weight as the objective functions.